WHEN THE TEACHER BECOMES THE STUDENT: YOUTH IMPACT ON PARENT TECHNOLOGY USE - Dworkin, Jodi; Brar, Pooja; Hessel, Heather (AoIR Selected Papers of Internet Research, 2018)
We are only beginning to understand the ways in which young people are introducing technologies into the family system and the ways that is impacting family relationships. What seems clear is that the face-to-face relationship does not translate directly to the online context, and online communication is not completely replacing in-person family relationships. Despite the lack of existing research, it is reasonable to expect that family relationships impact how youth and parents use online media. Building on socialization theory, in the current study we considered the ways in which youth technology use impacts parent technology use in parent-child dyads from India and the U.S. (98 dyads; youth: 37% female; mean age=17.3; parents: 54.6% female; mean age=41.5). When considering frequency of six types of technology use in a series of linear regression analyses: 1) general use to look for information, news, and use online tools, 2) audio or video calls, 3) texting, instant messaging, discussion boards, or email, 4) sending or receiving audio or video, and photos, 5) create or maintain blogs, microblogs, or websites, and 6) social networking sites, child technology use accounted for 8.4% to 27.0% of the variance in parent use. Despite the small sample size, it is clear that child technology use is strongly associated with parent use, even when considering diverse ways of using technology. Future research should use longitudinal data to explore how children impact parents’ technology use over time – how that influence changes with age, sociohistorical time and place, and life transitions.